CONSTRUCTION AND STANDARDISATION OF MATHEMATICS ANXIETY SCALE FOR UPPER-PRIMARY SCHOOL STUDENTS - Sethi, Sumati; Jalandharachari, A.S. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper elucidates the process of construction and standardization of the mathematics anxiety scale for upper-primary school students (class8) for which the investigator has collected data from 110 students of upper-primary level from both Govt. and private schools of Nayagarh district, Odisha. It has three stages- pre-try, try out-1 and try out-2 where in the pre-try-out phase, the investigator kept 60 items with 5 dimensions, and after getting the experts opinion and pilot study, the investigator kept 42 items in tryout-1 and in tryout-2, 34 items were selected for final scale by applying t-test for item analysis. The face validity and content validity were tested and reliability was tested by Cronbach’s alpha and which is 0.827 which was good in nature.